Philosophical Harmony: Understanding the Influence of Pedagogical Philosophy in Mathematical Teaching - Elfitra, Elfitra; Dewi, Izwita; Ahyaningsih, Faiz (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
This article investigates the profound implications of the application of pedagogical philosophy in mathematics teaching. Highlighting the key roles of constructivist philosophy, humanism, and ethics, the study discusses how these principles shape the way teachers approach mathematics teaching and influence student learning experiences. Through in-depth analysis, this article underlines the importance of philosophical harmony in creating an inspiring and effective learning environment. The integration of constructivist concepts emphasizes the active role of students in building their own knowledge, while the humanistic approach highlights aspects of creativity and personal development. In addition, this article explores how ethics can be integrated into mathematics learning, creating students who are not only technically skilled but also morally responsible. In conclusion, this article provides a deeper understanding of how pedagogical philosophy becomes a catalyst for positive transformation in mathematics teaching